Pemikiran Islam tentang Hubungan Negara dan Agama - Mohamad Harjum (Jurnal Adabiyah: Humanities and Islamic Studies, 2011)
The relation between religion and state according to Islam can be classified into three categories; Integrity, that is a concept which views that state and religion are two integrated institution which can be hand and hand organizing a political state. Secularism, a concept which describes that religion only organizes its own internal rules (relation between followers and God) without being intervented by state power; Simbiosism-mutualism, a concept viewing that religion and state are two aspect different, but need mutual help and understanding.